Destiny into Chance:: The Imperialist and the Périls of Nation Building - Kertzer, Jon (Studies in Canadian Literature / Études en littérature canadienne, 1999)
Nature and destiny are the traditional sanctions of nation building, the former assuring a stable identity, the latter motivating its development. For Sara Jeanette Duncan, nation building is perilous because nature and destiny prove to be rivals rather than allies. The style of The Imperialist is often so trenchant that it tests the rhetorical strategies through which Canada is built by showing that they do not operate effortlessly; that national identity and political freedom are not always mutually supportive; that historical chance is not easily transformed into national destiny. Four major rhetorical figures — heroic, mnemonic, domestic, and racial — jostle for positioning within a national imaginary that can never fully be articulated.